Perception and production of English vowels by native Iraqi Arabic learners - Abd, Ammar Abdul-Wahab (2016)
A crucial step in learning to communicate in a second language is to acquire its phonetic system. Accurate perception and production of the L2 phonemes set the groundwork for effective communication. However, speaking with accented-free pronunciation is difficult for EFL learners as everyone has a particular accent. No formal investigation, to the best knowledge of the researcher, investigated problems faced by Iraqi EFL learners. Moreover, L1 (Iraqi Arabic) influence on facilitating or complicating the acquisition of certain L2 (English) segments and how far L2 experience affects perception and production skills have not been investigated with this group of learners. There is also an ongoing debate on the relationship between perceptual abilities and production accuracy, and this study will fill these gaps in the literature. This study aims to investigate the perception and production of English vowels by Iraqi EFL learners to identify L1 influence and proficiency effects on these processes. The study also investigates the perception-production relationship. To achieve these aims, a word identification task and a reading task were conducted. Eighty-five Iraqi EFL learners participated in this study. They were divided into four groups based on their proficiency level. The results obtained from the word identification task and the results obtained from rating for the production task were analysed using various statistical tests. The results revealed that Iraqi EFL learners faced considerable difficulties in the perception and production of most vowels. Patterns of errors made by learners also indicated considerable similarities among the four groups, which suggests a systematic underlying influence on their perceptual and production behaviour. L1 influence was found to be a major factor in accounting for the results of this study. The L2 vowel space was also helpful in resolving inconsistent results. The learners’ performance revealed significant proficiency effects offering support to the experience effects hypothesized in the Speech Learning Model. However, proficiency effects were not identified among all groups or among all vowels suggesting that the acquisition of certain L2 phones did not improve due to perceptual reasons and/or L1 influence. The results showed that speech perception and production are significantly different from one another, indicating an asymmetrical relationship between them where speech production can be better developed than speech perception, particularly for the elementary group. The study concluded that the assumption that inaccurate perception should result in inaccurate production is not well supported in this study, especially among beginners. Current L2 speech learning models are generally successful in predicting and interpreting most of the difficulties encountered by Iraqi EFL learners; yet none of them can independently account for the all the data.